The pre- and postoperative nomograms to predict the textbook outcomes of patients who underwent hepatectomy for hepatocellular carcinoma - Xie, Gui-Lin; Liang, Lei; Ye, Tai-Wei; Xu, Fei-Qi; Wang, Dong-Dong; Xie, Ya-Ming; Zhang, Kang-Jun; Fu, Tian-Wei; Yao, Wei-Feng; Liu, Jun-Wei; Zhang, Cheng-Wu (Frontiers in Oncology, 2023)
Background & Aims: Increasing number of studies have confirmed that non-Textbook outcomes（non-TO）is risk factor of long-term outcome of malignant tumors. It is particularly important to identify the predictive factors of non TO for improving the quality of surgical treatment. We attempted to construct a nomogram for preoperative and postoperative prediction of non-TO after laparoscopic hepatectomy for hepatocellular carcinoma ( HCC ). Methods: Patients who underwent curative-intent hepatectomy for HCC between 2014 and 2021 at two Chinese hospitals were analyzed. Using univariate and multivariate analyses, the independent predictors of non-TO were identified. The prediction accuracy is accurately measured by the ROC curve and calibration curve. Results: Among 515 patients, 286 patients (55.5%) were not achieve TO in the whole cohort. Seven and eight independent variables were incorporated into the nomograms for predicting non-TO, respectively. The area under the receiver operating characteristic curves (AUCs) of The two nomograms achieved 0.698 and 0.762, which were significantly higher than the Child-Pugh grade, 8th TNM staging, BCLC staging; meanwhile, the calibration curves for non-TO probabilities fitted well. Conclusions: Our proposed nomogram resulted in accurate prediction of non-TO following laparoscopic resection of HCC, which may guide clinicians to make individualized surgical decisions, improve postoperative survival, and plan adjuvant therapy against recurrence.